Inuit perceptions of climate change in East Greenland - Buijs, Cunera (Études/Inuit/Studies, 2010)
AbstractGlobal warming and climate change are important topics of debate in Greenland. This paper examines how the Tunumiit of East Greenland perceive the weather, the changing climate, and the local environment. It also discusses how their perceptions have been influenced by political debates on global warming, sustainable development, and wildlife management since the 1950s. In the past, if some animal species disappeared from a specific area, or if the weather turned bad, the Tunumiit would attribute this misfortune to human transgressions of rules of respect. Today, they often connect the increasingly unpredictable weather to their reduced access to natural resources and greater difficulties in travelling. Some hunters speak of a shift from seal hunting to cod fishing in East Greenland, although fishing is still perceived as a vulnerable source of income with low status. Nowadays, older methods of navigation and orientation coexist with such new technologies as GPS and mobile telephones. Some local hunters and villagers feel unfairly accused of increases in CO2 emissions and pollution from their motorboats and generators. Tunumiit hunting communities are facing increasing uncertainty on all levels of their existence, and their hunters are turning to the growing tourism industry—a side effect of global warming—and other coping strategies to maintain their local subsistence activities and to reinforce their own culture.